Social studies excursions, K-3. Book three, Powerful units on childhood, money, and government - Alleman, Janet; Brophy, Jere E.; Knighton, Barbara; Miller, Danny (Portsmouth, NH : Heinemann, 2003)
A guide to creating educational units on childhood, money, and government for students in grades K through three.
Includes bibliographical references (p. 297-299).
Professional
Keywords: Social sciences -- Study and teaching (Primary); Social sciences -- Study and teaching